PERSEPSI KARYAWAN TENTANG KONFLIK KERJA DI SOFYANINN HOTEL RANGKAYO BASA PADANG - Andika, Putri; Yuliana, Yuliana; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study aims to determine employee perceptions about workplace conflict in SofyanInn Hotel Rangkayo Basa Padang, which includes three indicators of labor conflict, namely: emotion (emotion), values (values) and interest (interest). This type of research is descriptive quantitative research. The study population was the employees SofyanInn Hotel Rangkayo Basa Padang except manager. Employees SofyanInn Hotel Rangkayo Basa Padang totaled 27 permanent employees and 5 daily worker, so that the total population of 32 people. The sampling technique in this research is non probability sampling is saturated sampling a total of 32 employees. The data collection techniques with indirect communication by distributing a questionnaire (questionnaire) in the form of Likert scale that has been tested for validity and reliability. The results showed that the general perception of a conflict of employees working in SofyanInn Hotel Rangkayo Basa Padang belong to the category of poorly with the average value of 115.44 which was in the range 88,1≤X <117.3. While based on individual indicators, namely: 1) Emotion (emotion) employees SofyanInn Hotel Rangkayo Basa Padang belong to the category of poorly with an average value of 61.44 is in the range of scores 50,1≤ X <66.6, 2 ) Values (value) Basa Rangkayo employees SofyanInn Hotel Padang classified in the category quite well with an average value of 39.06 is in the range 34,7≤X score <43.2, 3) Interest (interest) employees SofyanInn Hotel Rangkayo Basa Padang belong to the category of poorly with an average value of 14.94 is in the range 12 scores ≤ X <15.9.